Climate Change Implications on Strategic Tourism Development of Yogyakarta during the Pandemic Covid-19 - Isdarmanto; Kiki Rizki Makiya; Irra C. Dewi (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2022)
The purpose of this research is to the regional tourism development strategy in DIY Province to answer the challenges of climate change impacts related to the community’s social life and tourism which was very-slumped during the pandemic. What are the efforts of the community and government to restore tourism? The existence of diverse and unique potential of DIY's natural resources must be maintained and developed even during the pandemic. Strategic innovation to create regional competitive advantage through increasing community empowerment and the role of the Penta helix. This study uses qualitative research methods, through field observations, interviews, and empirical document data that are appropriate and relevant to the research objectives. The commodification of natural potential and the role of the Penta helix can encourage people to build micro-entrepreneurs, culinary businesses, restaurants, cafes, baristas, and online delivery businesses in DIY. In the future, this research is expected to be redeveloped as a reference for new tourism development strategies with more creative and adequate designs as a competitive advantage for tourism according to the demands of millennial tourism development.